(untitled) (Scientific journal of the Fergana State University, 2023)
This article analyzes the description of phraseologies related to the names of creatures in German and Uzbek. Consideration of phraseological units of animal names in the lingvoculturological context allows to analyze the features of their functioning. In the process of studying the expressions of the German and Uzbek languages, the prevalence of phraseological units associated with the names of animals has shown that it is absolutely true. The abundance of such phrases, their figurative descriptions, and the anthropocentric nature of their activities determine the interest of linguists and lexicographers in this part of the phraseological fund. In the phraseology of both languages, there are many images of different animals, insects and birds. In the process of analysis, it can be concluded that the study of zoomorphic figurative phraseological units in German and Uzbek languages ​​shows that they are microsystems within the general phraseological system of both languages. The contrasting analysis of the names of German and Uzbek phraseological units made it possible to identify similarities and differences in descriptive-based descriptions.